The territorial development of Mukachevo's eparchy in the Middle Ages and the early modern period - Vavrinec Žeňuch (CES Working Papers, 2020)
The history of each ecclesiastical territory unit affected its region. The origin of Mukachevo's eparchy is unique especially since it is the eparchy which was not governed by any ecclesiastical or state nobility. This matter shapes it into the distinctive model of the formation of an autonomous ecclesiastical unit. The forming of parochial and structure is related to Wallachian colonisation and following development of this region in modern times. The goal we established is an analysis of first events, which related to the formation of Mukachevo's eparchy title, later we follow the development of the title of the eparchy itself as long as its jurisdictional territory until the year 1771.
Keywords: 330; Mukachevo's eparchy; Orthodox people; ecclesiastical administration; Greek Catholics; Hungary